Fits, feet and HIV: lessons from a case of coexisting epilepsy and neuropathy in a patient with perinatally acquired HIV-1 infection. (16th October 2018) - Freeman-Romilly, Nell; Mewasingh, Leena; Coomer, Annette; Foster, Caroline
Abstract : An 18-year-old black African man with well-controlled perinatally acquired HIV-1 was diagnosed in late adolescence with the unrelated diagnoses of Charcot-Marie-Tooth type 1A (CMT1A), epilepsy due to polymicrogyria and subsequently developed severe depression. The CMT1A diagnosis occurred after transfer of care from a local paediatric HIV service to a tertiary paediatric referral centre and was precipitated by recognition of a history and neurological signs not typically associated with perinatal HIV. The case resulted in the establishment of a quarterly combined paediatric HIV and paediatric neurology multidisciplinary team clinic to assess children and adolescents living with HIV with neurological symptoms.